Copper‐Catalyzed [3+2] Annulation of 2‐Arylidene‐1, 3‐Indandiones with N‐Acetyl Enamides for the Synthesis of Spiropyrrolines. Issue 3 (20th December 2019) - Duan, Jindian; Mao, Yiyang; Zhang, Lei; Zhu, Ning; Fang, Zheng; Guo, Kai
Abstract: A copper‐catalyzed intermolecular [3+2] annulation of 2‐arylidene‐1, 3‐indandiones with N‐acetyl enamides has been developed to assemble spirocyclic pyrrolines, which are important building blocks for organic synthesis and drug discovery. This heteroannulation protocol tolerates various functional groups and proceeds in good to excellent yields. Mechanistic studies reveal that the reactions might involve radical processes. 1‐Pyrrolines are important core structural constituents of numerous naturally occurring compounds and pharmaceuticals. [1] On the other hand, spiroindane‐1, 3‐diones have been the focus of considerable attention due to their prevalence in many natural products that possess varied and extensive biological activities, which include antitumor, antibiotic, [2] and antiproliferative activity on HL60 and apoptosis resistant leukemia cell lines. [3] Accordingly, a number of synthetic strategies have been investigated to construct these skeletons. [4] Considering the biomedical importance of the two classes of compounds, the introduction of spiroindane‐1, 3‐dione group into the pyrroline core structure may further broaden the utilization of these compounds and potentially benefit drug‐discovery efforts. [5] Abstract :